Clinical Evaluation of Acute Pancreatitis Caused by SARS-CoV-2 Virus Infection - Hulya Vatansev; Mehmet Aykut Yıldırım; Serkan Kuccukturk; Mehmet Ali Karaselek; Cengiz Kadiyoran (Gastroenterology Research and Practice)
Introduction. Coronavirus 2019 disease (COVID-19), caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), has spread to more than 200 countries worldwide. We aimed to present acute pancreatitis (AP) cases caused by SARS-CoV-2 viral infection. Methods. The study was conducted retrospectively between April 2020 and June 2020 in Necmettin Erbakan University Meram, Medical Faculty Hospital, and 150 hospitalized patients diagnosed with COVID-19 were included. The degree of acute pancreatitis was determined according to the Atlanta classification. Organ failures of the patients were evaluated in terms of respiratory, cardiovascular, and nephrology according to the modified Marshall scoring (MMS) system, and CTSI (Balthazar score) and Imrie score were determined. Modified Marshall score≥2 was considered organ failure. Results. A total of 29 patients were diagnosed with acute pancreatitis. All 29 patients with pancreatitis had respiratory failure during hospitalization. After the diagnosis of pancreatitis, there was no change in respiratory failure. According to the Atlanta classification, 19 patients had mild AP and 10 patients had moderate AP. Patients with acute pancreatitis were scored according to the CTSI (Balthazar score), and there were no patients with ≥6 severe pancreatitis. The CTSI score of 4 patients was 3. In addition, the Imrie score of the patients was determined and 8 patients with Imrie score≥3 were identified. Conclusion. The rate of pancreatic damage in SARS-CoV-2 infection was found to be 19% (n=29) in our study. In our study, we highlight acute pancreatitis as a complication associated with COVID-19 and the importance of pancreatic evaluation in patients with COVID-19 and abdominal pain is demonstrated.